2017
DOI: 10.3174/ajnr.a5500
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Factors Associated with Postnatal Brain Injury in Infants with Congenital Diaphragmatic Hernia

Abstract: Fetal lung hypoplasia is associated with postnatal brain injury in congenital diaphragmatic hernia, suggesting that the severity of lung disease and associated treatments affect brain health as well. We found no evidence of prenatal brain parenchymal injury or maturational delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Firstly, the presence of these symmetrically distributed hypogyria areas suggests altered volumetric growth and maturation as it has been already seen in other postnatal CDH neuroimaging studies [ 12 , 13 , 15 , 32 ]. In particular, such altered maturation was actually assumed as the results of reduced myelination, cortical infolding [ 12 ] and delayed sulcation [ 14 ] occurring in CDH infants. Neuroimaging investigations had already shown evidence of brain injury, including parenchymal abnormalities and enlarged extra-axial spaces as the most common findings, usually attributed to delayed brain maturation [ 38 ], but no evidence of subtle alterations of cortical parameters has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Firstly, the presence of these symmetrically distributed hypogyria areas suggests altered volumetric growth and maturation as it has been already seen in other postnatal CDH neuroimaging studies [ 12 , 13 , 15 , 32 ]. In particular, such altered maturation was actually assumed as the results of reduced myelination, cortical infolding [ 12 ] and delayed sulcation [ 14 ] occurring in CDH infants. Neuroimaging investigations had already shown evidence of brain injury, including parenchymal abnormalities and enlarged extra-axial spaces as the most common findings, usually attributed to delayed brain maturation [ 38 ], but no evidence of subtle alterations of cortical parameters has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Tracy et al reported abnormal prenatal neuroimaging findings in only 4 CDH patients, one of which had an abnormal cortical gyration pattern [ 15 ]. Recently, both traditional [ 14 ] and morphological [ 16 ] MRI investigation were performed on CDH fetuses, revealing associations between prenatal and postnatal enlarged extra-axial spaces, but an absence of delayed sulcation and parenchymal abnormalities in fetuses. Since brain parenchymal injury was absent in fetuses and appeared in the postnatal stage, they hypothesized that cortical alteration might be related to postnatal factors such as NICU stay, ECMO or surgery [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations